Experience of feeding with liquid ready milk formula in infants with low and extremely low body weight in resuscitation intensive care department - K.D. Gorelik; Yu.V. Gorelik (Вопросы современной педиатрии, 2011)
The article analyzes an experience of feeding with liquid ready formula Similac Special Care as a product for initial enteral feeding in children with extremely low and very low body weight (n = 31, body weight — 800–1600 g). Children started nutrition with the formula on an average at 4th day of life with progressive increase of its volume up to 100% of common enteral feeding. The registration of actual intake of energy and protein, volume of food and body weight was performed daily. Enteral feeding with ready formula didn’t show any complication in all patients. Stable increase of body weight was shown after transition to complete enteral feeding. Sterility of liquid formula provides additional protection from possible bacterial contamination of food and excludes «human factor» at the time of its preparation.Key words: children, extremely low and very low body weight, enteral nutrition, liquid formula.